Coordination models and languages : 9th International Conference, COORDINATION 2007 Paphos, Cyprus, June 6-8, 2007 : proceedings - COORDINATION; Murphy, Amy L.; Vitek, Jan (Lecture Notes in Computer Science, 2007)
This book constitutes the refereed proceedings of the 9th International Conference on Coordination Models and Languages, COORDINATION 2007, held in Paphos, Cyprus, June 2007, as one of the federated conferences on Distributed Computing Techniques. It examines how to increase modularity, simplify reasoning, and ultimately enhance today's software development by exploring the spectrum of languages, middleware, services, and algorithms.